Antagonistic Interactions Between Soil-Isolated Actinomycetes and Pathogenic Bacterial Strains - Ayat Abdalmutalib Mahdi; Sajjad Falah Hassan; Rawan abdulkadir zaki; Hiba Tawfiq Ali; Jenan Atiyah Ghafil; Ayaid Khadem Zgair (World Journal of Experimental Biosciences, 2024)
Bacterial resistance to commonly used antibiotics for treating infections is the biggest challenge facing clinicians. Previous research on antibiotic-producing actinomycetes has been limited. This study aims to explore the potential of identifying actinomycete isolates that may produce antibiotics more effective than current treatments for bacterial infections. Fifty soil samples were collected from various regions in central Iraq to isolate actinomycetes. Ten clinical bacterial isolates of Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Enterococcus faecalis, which were resistant to multiple antibiotics, were obtained and maintained for use in experiments. The double-layer of agar and spot assay was used to detect antagonistic interactions between actinomycete and pathogenic bacterial isolates (ten isolates). The Kirby-Bauer method was employed to evaluate the response of these isolates to four different antibiotics (ofloxacin (OF), gentamicin (CN), amoxicillin (AX), vancomycin (VA). The experiments demonstrated successful isolation of actinomycetes and validated the effectiveness of the employed method. The results indicated that the clinical isolates were highly resistant to the antibiotics tested. Nine out of ten isolates showed antagonistic reactions to actinomycete bacteria. This suggests that soil-derived actinomycetes can be isolated and possess strong antagonistic activity against bacteria resistant to various antibiotics. Such isolates could potentially be used to develop more effective antibiotics than those tested in this study.
Keywords: Actinomycetes, Antagonism, Antibiotics, Clinical pathogenic bacteria.